2014
DOI: 10.1016/j.molonc.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

HER family kinase domain mutations promote tumor progression and can predict response to treatment in human breast cancer

Abstract: Resistance to HER2-targeted therapies remains a major obstacle in the treatment of HER2-overexpressing breast cancer. Understanding the molecular pathways that contribute to the development of drug resistance is needed to improve the clinical utility of novel agents, and to predict the success of targeted personalized therapy based on tumor-specific mutations. Little is known about the clinical significance of HER family mutations in breast cancer. Because mutations within HER1/EGFR are predictive of response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…However, HER‐2 activating mutations, another novel modus to activate HER‐2, have been reported 41, 42. Bose and his colleagues identified 16 HER‐2 somatic mutations though cancer genome sequencing in HER‐2 gene amplification‐negative breast cancer patients.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 99%
“…However, HER‐2 activating mutations, another novel modus to activate HER‐2, have been reported 41, 42. Bose and his colleagues identified 16 HER‐2 somatic mutations though cancer genome sequencing in HER‐2 gene amplification‐negative breast cancer patients.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 99%
“…Finally, in the larger scale, Centrosome amplification (CA) amongst particular breast cancer subtypes (Her2+ subtype) is associated with genomic instability and aggressive tumor phenotypes., and Lee et al (2014) concluded CA, the precursor of chromosome instability and polyploidy correlates with amplification of the Her2 receptor, which affects over 20% breast cancer patients (Lee et al, 2014), In the study, they also clarified SGOL1 (Shugoshin proteins) is an attractive target for blocking the progression., when referred to the instability, we found another interesting outcome-HER family mutations in breast cancer may matter much, but until now, Little is known about the clinical significance, In the newest study of Delphine R et al HER2 mutants conferred an aggressive phenotype and altered effects of the TKI lapatinib (Boulbes et al, 2014), these coincided with JULIANN CHMIELECKI's declare that mutations can also activate the ERBB2/HER2 gene in breast, while at the same time be similarly sensitive to ERBB2/ HER2 inhibitors (Chmielecki et al, 2014). Joyfully, about the mutant mechanism, researchers newly reported a case that a breast cancer patient harboring an activating EGFR mutation clinically benefiting from EGFR-targeted treatment (Ali et al, 2014).…”
Section: Other Associated Micromoleculesmentioning
confidence: 90%
“…And the HER2 gene has been established as a valid biological marker for the treatment of breast cancer So far, Small Molecule Tyrosine Kinase Inhibitors of HER2 such as Trastuzumab, Pertuzumab, Lapatinib, Afatinib, AZD8931, AST-1306, AEE-788, CI-1033 (Canertinib), CP-724714, CUDC-101, TAK-285, AC-480 (BMS-599626), PF299804, PF299 (Dacomitinib), EKB-569 (Perlitinib) are on their way to clinical use or undergoing phase trials in aggressive breast cancer (Kumler et al, 2014;Schroeder et al, 2014), being explored for their potential to inhibit EGFR and HER2 tyrosine kinases. But we can't delay the fact that HER2 mediated resistance via multiple mechanisms is a common clinical problem (Boulbes et al, 2014;Leivonen et al, 2014). And treatment-induced toxicity, which can impair quality of life can't be ignored (Barroso-Sousa et al, 2013).…”
Section: Treatment Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Among the EGFR alterations, mutations in the kinase domain have been found in 7, 89 % of HER2-positive BC patients [21]. EGFR overexpression by IHC was positive in approximately 22.2 % (86/388) of BC patients [22].…”
Section: Egfrmentioning
confidence: 99%